Quantifying the effect of diagenetic recrystallization on the Mg isotopic composition of marine carbonates. (1st May 2017) - Chanda, Piyali; Fantle, Matthew S.
Abstract: The Mg and Sr isotopic compositions (δ 26 Mg and 87 Sr/ 86 Sr) of pore fluids and bulk carbonates from Ocean Drilling Project Site 1171 (South Tasman Rise; 2148.2 m water depth) are reported, in order to evaluate the potential of diagenesis to alter carbonate-based geochemical proxies in an open marine system. Given the trace amounts of Mg in marine carbonates relative to coexisting pore fluids, diagenesis can alter carbonate δ 26 Mg, a promising proxy for seawater δ 26 Mg that may help elucidate long-term changes in the global Mg cycle. Constraints on the effect of diagenetic recrystallization on carbonate δ 26 Mg are therefore critical for accurate proxy interpretations. This study provides context for assessing the fidelity of geochemical proxy-reconstructions using the primary components (i.e., foraminiferal tests and nannofossils) of bulk carbonate sediments. We find that pore fluid δ 26 Mg values (on the DSM3 scale) at Site 1171 increase systematically with depth (from −0.72‰ to −0.39‰ in the upper ∼260 m), while the δ 26 Mg of bulk carbonates decrease systematically with depth (from −2.23‰ to −5.00‰ in the upper ∼260 m). This variability is ascribed primarily to carbonate recrystallization, with a small proportion of the variability due to down-hole changes in nannofossil and foraminiferal species composition. The inferred effect of diagenesis on bulk carbonate δ 26 Mg correlates with down-core changes in Mg/Ca, Sr/Ca, Na/Ca, and 87 Sr/ 86 Sr. A depositional reactive-transport model is employed to validate the hypothesis that calcite recrystallization in this system can generate sizeable shifts in carbonate δ 26 Mg. Model fits to the data suggest a fractionation factor and a partition coefficient that are consistent with previous work, assuming calcite recrystallization rates of ⩽7%/Ma constrained by Sr geochemistry. In addition, either partial dissolution or a distinctly different previous diagenetic regime must be invoked in order to explain aspects of the elemental chemistry and 87 Sr/ 86 Sr of relatively deep sediments from Holes A and C. This study indicates that the dynamics of a given sedimentary system can significantly alter bulk carbonate geochemistry, and presents a framework for considering the potential impact of such alteration on picked archives such as foraminiferal tests and nannofossils. Ultimately, this study contributes to the development of δ 26 Mg as a proxy for seawater δ 26 Mg by quantifying the susceptibility of carbonate δ 26 Mg to diagenetic alteration, particularly in sediments in open marine systems. This study suggests that because of the sensitivity of carbonate δ 26 Mg to diagenetic recrystallization, it can, in certain systems, be used to quantify the impact of diagenesis on carbonate-based geochemical proxies.